Fiscal Transparency and Government Credit Quality: Evidence from the U.S. States. Issue 2 (4th March 2021) - Yu, Jinhai; Wei, Wenchi; Butler, J. S.
Abstract: This article examines the effect of the U.S. state governments' fiscal transparency on their credit quality. Although government credit quality essentially measures the debt default risk, it can potentially be viewed as a proxy for government fiscal performance. We primarily argue that government fiscal transparency reduces information asymmetry in the municipal bond market and thus increases government credit quality. Data on credit quality (ratings) are collected from Standard & Poor's, and fiscal transparency is measured by a well-established index that captures multiple institutional and managerial features of state budgeting processes. To address the potential endogeneity problem of fiscal transparency, we use control functions and measures of political competition as instrumental variables. The empirical results show that fiscal transparency positively affects state credit quality. The findings enhance a deeper understanding of the consequences of fiscal transparency and the determinants of government credit quality.